G271(P) Parental migration for labour and health in children and adolescents left-behind children: a systematic review and meta-analysis. (May 2019) - Fellmeth, G; Rose-Clarke, K; Zhao, C; Busert, LK; Zheng, Y; Massazza, A; Sonmez, H; Eder, B; Blewitt, A; Lertgrai, W; Orcutt, M; Ricci, K; et al.
Abstract : Background: The number of people migrating for labour is growing around the world, particularly in low- and middle-income countries. Parents often move for work, leaving their children behind. In China alone there are 61 million left-behind children and adolescents (LBCA). Methods: We conducted a systematic review including studies on parental migration and LBCA aged 0–19 years in low- and middle-income countries. Our outcomes were the 10 main causes of disability-adjusted life years in the under-5, 5–9 and 10–19 year age groups. These included nutrition, mental health, unintentional injuries, infectious disease, substance use, unprotected sex, early pregnancy and abuse among. We searched databases including MEDLINE, EMBASE and CINAHL from inception to April 2017, with no language restrictions. We conducted meta-analyses, sensitivity analyses based on the quality of studies, subgroup analyses (internal and international migration and one or two parent absence), and meta-regression to investigate child gender and age. A revised version of the Newcastle-Ottawa tool was used to assess bias. The protocol was registered with PROSPERO (CRD42017064871). Results: We identified 111 studies, including 2 64 967 children and adolescents. 91 studies were conducted in China, all of which focused on internal migration. The other 20 studies were largely related to international migration in Asia. LBCA had an increased risk of depression (risk ratio (RR) 1.52; 95% confidence interval (CI) 1.27, 1.82) and higher depression scores (standardised mean difference (SMD) 0.16; 0.10, 0.21), anxiety (RR 1.85;95% CI 1.36, 2.53 and SMD 0.18; 95% CI 0.11, 0.26), suicidal ideation (RR 1·70; 95% CI 1.28, 2.26), conduct disorder (SMD 0.16; 95% CI 0.04, 0.28) and substance use (RR 1.24; 95% CI 1.00, 1.52). There was an increased risk of malnutrition: wasting (RR 1.13; 95% CI 1.02, 1.24) and stunting (RR 1.12; 95% CI 1.00, 1.26). We found no difference for other nutrition outcomes, unintentional injury, abuse or diarrhoea. Removing low quality studies made little difference to the outcomes, as did subgroup analyses. Meta-regression showed no significant effect of gender or mean age on any outcomes. Conclusions: Parental labour migration is associated with morbidity in LBCA, with no evidence of any benefit. The strongest evidence exists in China, with more research required in the rest of the world.